Differential expression of SDF-1 receptor CXCR4 in molecularly defined forms of inherited thrombocytopenias. (18th August 2017) - Salim, Juan P.; Glembotsky, Ana C.; Lev, Paola R.; Marin Oyarzún, Cecilia P.; Goette, Nora P.; Molinas, Felisa C.; Marta, Rosana F.; Heller, Paula G.
Abstract: The SDF-1-CXCR4 axis plays an essential role in the regulation of platelet production, by directing megakaryocyte (MK) migration toward the vascular niche, thus allowing terminal maturation and proplatelet formation, and also regulates platelet function in an autocrine manner. Inherited thrombocytopenias (IT) comprise a spectrum of diverse clinical conditions caused by mutations in genes involved in platelet production and function. We assessed CXCR4 expression and SDF-1 levels in a panel of well-characterized forms of IT. Decreased surface CXCR4 levels were found in 8 of 27 (29.6%) IT patients by flow cytometry, including 4 of 6 patients with ANKRD26 -RT, 3 of 3 patients with GPS and 1 of 6 patients with FPD/AML. Low CXCR4 levels were associated with impaired SDF-1-triggered platelet aggregation, indicating that this decrease is functionally relevant, whereas a normal platelet response was shown in patients harbouring preserved membrane CXCR4. Reduced CXCR4 was not due to decreased gene expression, as platelet RNA levels were normal or increased, suggesting a post-transcriptional defect. Increased ligand-induced receptor internalization was ruled out, as circulating SDF-1 levels were similar to controls. MK CXCR4 expression was normal, indicating that the defect in CXCR4 arises after the step of platelet biogenesis. In conclusion, the finding of defective CXCR4 expression specifically associated with certain IT disorders highlights the fact that abnormalities in several megakaryocytic regulators underlie IT pathogenesis and further reveal the heterogeneous nature of these conditions.